Pengaruh Model Pembelajaran Teaching Factory Dan Keterlibatan Siswa Terhadap Kesiapan Kerja Siswa Dengan Motivasi Sebagai Variabel Mediasi Pada Siswa SMKN 1 Surabaya - Kavilla Hercyndana; Novi Trisnawati (Jurnal Kajian Ilmu Pendidikan (JKIP), 2026)
This research is motivated by the importance of work readiness of vocational high school students in facing the demenas of the world of work. Work preparation is not only influenced by technical skills, but also by the learning process implemented in schools and students psychological fctors. Teaching Factory based learningf, student engagement, student motivation. This study aims to analyze the effect of Teaching Factory based learning and student engagement on students work readiness with motivation as a mediating variable. This study uses a quantitative approach with the Partial Least Square-Structural Equation Modeling (PLS-SEM) data analysis method assisted by SMART PLS 4.1.1.6 software. The study population included 139 grade XII students majoring in Office Management & Business Services at SMKN 1 Surabaya with a sampling technique using Proportionate Stratified Random Sampling. The results of the study showed that Teaching Factory learning and student engagement significantly influenced student work readiness. Student engagement also influenced motivation, while Teaching Factory had no significant effect on motivation. However, motivation mediated the influence of Teaching Factory and student engagement on student work readiness.